Розвиток аграрного маркетингу в Україні - Кобернюк, Сергій Олександрович; Koderniuk, Serhii (Інститут підготовки кадрів державної служби зайнятості України, ТОВ `Редакція журналу `Економіка та держава`, 2019)
У статті описано сучасний стан розвитку агромаркетингу в Україні. Розглянуто різні підходи до трактування сутності поняття "агромаркетинг" і виявлено, що не існує єдиного підходу до трактування сутності цього поняття. Запропоновано власне трактування агромаркетингу, яке являє собою діяльність сільськогосподарських підприємств направлену на доведення інформації про товар до споживачів, яка пов'язана з вивченням потреб на ринку для отримання максимального прибутку. Вивчено стан маркетингу в Україні при адміністративно-регульованій та при ринковій економіках. Досліджено нормативно-правову базу, яка регламентує маркетингову діяльність в аграрному секторі країни. Визначено формування системи сучасного аграрного маркетингу, яка включає інфраструктуру маркетингу, систему стратегічного й оперативного управління, систему інформаційного забезпечення, систему управління агромаркетингом, систему агромаркетингових досліджень. The article describes the current state of development of agromarketing in Ukraine. Different approaches to the interpretation of the essence of the concept of "agromarketing" are considered and it is found that there is no single approach to the interpretation of the essence of this concept. We propose a proper interpretation of agromarketing, which is the activity of agricultural enterprises aimed at bringing information about goods to consumers, which is related to the study of market needs for maximizing profits. The state of marketing in Ukraine under the administrative-regulated and in the market economies is studied. The regulatory and legal framework regulating marketing activity in the agricultural sector of the country is explored. The formation of the system of modern agrarian marketing, which includes the marketing infrastructure, the system of strategic and operational management, the system of information support, the control system of agromarketing, the system of agromarketing research, was determined. The system of informational support covers the formation of information status of raw materials, auxiliary and finished products. The management system of agromarketing enables to form the organizational structure of marketing management with the foreseen distribution of rights, tasks, responsibilities in the marketing departments; modernize the principles of personnel management, personnel selection; development of job descriptions. The directions of marketing research are constantly expanding. Current research suggests conducting marketing research, starting with market conditions; consumer research, their purchasing behavior; study of individual commodity groups; analysis of firm structure of the market (competitors, suppliers, intermediaries); research of the internal environment of enterprises, commodity, price, marketing, communication policy; study of consumer properties of products and directions for improving its qualitative characteristics. The development of the strategy of agromarketing includes the development of tactical tasks for implementing a strategic marketing plan; the ranking of tasks and a step-by-step control over the course of their implementation in all subdivisions.
Agricultural market development in Ukraine
Keywords: агромаркетинг; agromarketing; аграрний сектор; agrarian sector; сільськогосподарські підприємства; agricultural enterprises; сільськогосподарська продукція; agricultural products; системи аграрного маркетингу; agrarian marketing systems; збут (реалізація) продукції; sales (sales) of products